Long‐Term Outcomes of Multidisciplinary Rehabilitation for Chronic Musculoskeletal Pain. (21st April 2016) - Volker, Gerard; van Vree, Félicie; Wolterbeek, Ron; van Gestel, Marc; Smeets, Rob; Köke, Albère; Vlieland, Theodora Vliet
Abstract: Objectives: Evidence for the effectiveness of multidisciplinary rehabilitation for chronic musculoskeletal pain (CMP) has been reported but its outcomes in the longer term and in mixed groups of chronic pain patients are largely unknown. The aim of the present study was to describe the two‐year outcomes of a 15‐week multidisciplinary pain rehabilitation programme in patients with mixed CMP in terms of pain, activities, participation and healthcare usage. Methods: Data were recorded routinely at admission, discharge, and at three, 12 and 24 months' follow‐up for all consecutive patients with CMP referred to a rehabilitation programme over a 21‐month period. The 15‐week multidisciplinary rehabilitation programme consisted of cognitive behavioural therapy and exercise, as well as individual and group sessions with additional treatment modalities. Assessments included the Pain Disability Index (PDI), the Pain Catastrophizing Scale (PCS), the Multidimensional Pain Inventory (MPI) and numerical scales for pain and fatigue. Moreover, the RAND‐36‐Item Health Survey ('RAND‐36') and questions on healthcare usage and work status were administered at admission, and at 12 and/or 24 months. Paired t ‐tests, Wilcoxon signed‐rank tests, McNemar tests and mixed‐model analyses were used to analyse changes over time. Results: A total of 165 patients were included initially [mean age 44.1 (standard deviation 12.9) years], 143 of whom (87%) were women, with data from 125 (76%) and 120 (73%) patients being available at 12 and 24 months' follow‐up, respectively. All outcomes showed statistically significant improvements between admission and discharge, and at three, 12 and 24 months' follow‐up ( p < 0.05). At 24 months, the median number of different healthcare providers visited in the previous year had decreased significantly compared with that at admission [from a median of 4 (range 1–13) to a median of 2 (range 0–9)], and within the group of patients working at admission (50%), the proportion of those working 25 hours or more per week had increased significantly from 16% to 48%. Conclusions: Improvements in pain and functioning seen directly after a 15‐week multidisciplinary treatment programme for patients with CMP were maintained, health care usage decreased and the number of working hours among working patients increased at 24 months' follow‐up. Future studies are needed to examine if additional interventions after discharge can enhance further the favourable results. Copyright © 2016 John Wiley & Sons, Ltd.